CODE SWITCHING IN NATURALIZED INDONESIAN FOOTBALL PLAYER’S INSTAGRAM CAPTION - Nasution, Atikah Auni; Silvizi Hijra, Hannah Zakiyya; Fianda, Afiqah; Sianturi, Naomi Elisabeth; Rangkuti, Rahmadsyah (Ma Chung Press, 2024)
This research investigates the phenomenon of code-switching in naturalized Indonesian football players' Instagram captions, with a particular focus on how audience perceptions are affected. This research used Poplack's code-switching theory (1980) to analyze Instagram captions. This research used qualitative method to collect data from 2024 Instagram posts of naturalized football players. The research results show that 43 code-switching was found in naturalized Indonesian football players' Instagram captions. 21% are intra-sentential switching, and 79% are inter-sentential switching. Meanwhile, no tag switching is identified. A number of code-switching are dominated by inter-sentential code-switching. The 70 comments received from the audience were overwhelmingly positive, with 93% of respondents praising and supporting the players' adaptation to Indonesian culture. In conclusion, this research highlights the frequent use of code-switching in Instagram captions by naturalized Indonesian football players. This enables players to communicate more effectively and represent their diverse backgrounds, which positively shapes audience perception.